The Pinisi Festival as a Tourist Attraction in Bulukumba District of South Sulawesi - Siryayasa, Nyoman; Jam'an, Andi (Journal of Indonesian Tourism and Development Studies, 2020)
The Pinisi Festival is a national tourism event. The festival is expected to develop the tourism industry in Bulukumba Regency. This study aims to describe and discover the Pinisi Festival's performance and influence as a tourist attraction. This study is qualitative research with a descriptive approach. The used data collection techniques of this research were observation, in-depth interview, and literature study. The results of this study showed that the Pinisi Festival was held for three days with a variety of activities, i.e. Opening Ceremony, Pinisi Trip from Leppe' Eto Bira, Fishing Contest, GEMARI (Eat Fish Movement) Campaign, Traditional Pinisi Launching Ritual, Bergem Bira Parade, The Andingingi Kampong Traditional Ritual, Crowbar Burns Ritual, Pinisi Expo, Bulukumba Traditional Dance Performance, Bulukumba Traditional Culinary Festival, and Photography Jamboree. The Pinisi Festival has an impact on increasing the number of both domestic and foreign tourists or increasing of 70% from the previous few months so that it can be used as a media promotion of the tourism development in Bulukumba. Keywords: Pinisi Festival, tourist attraction, tourism event.